Qumran Hebrew Qal Prefix Conjugation Forms with Mater w after the First Radical Or: ‮htsṿrh ʾṿmrt tdṿrshny‬‎ - Stadel, Christian 1982- (2024)
Forms like ‮ידורשהו‬‎, viz. qal stem prefix conjugation forms with an object suffix in which a mater lectionis indicates the presence of a rounded vowel after the first radical, constitute the only unique Qumran Hebrew morphological trait that has no parallels in other traditions of the language. In this paper, I suggest a new explanation for the development of these forms (and of orthographically similar qal stem imperatives and infinitives). While previous research tried to explain the forms as resulting from analogy, I propose that they are (by and large) the result of regular sound change: vowel deletion of the unstressed stem vowel followed by the emergence of an epenthetic copy vowel that originated in the masculine plural forms.
Keywords: anaptyxis; vowel deletion; prefix conjugation; Morphology; Phonology